Knowledge and Attitude of the Farmers towards Raised bed and other Improved Production Technology of Pigeonpea (Cajanus cajan) for Climate Resilient Agriculture - Abhay Kumar Singh , Dalbeer Singh , Aarti Singh , Abhishek Singh , Mukesh Singh; Anjani Kumar (Indian Journal of Extension Education, 2016)
The present study was undertaken to find out the knowledge and attitude of the farmers towards raised bed and other improved technology of pigeonpea. Raised bed sowing of pigeonpea is still in its infancy in India and there is a need to make it popular among the farmers. Though there is a phenomenal growth in the area under Raised bed sowing of pigeon pea, a lot of work is still to be done to explain and convince the farmers, especially those in the dry land area about the high potentialities of this new technique. The present study was conducted in Pataudi block of Gurgaon district in Haryana, which was selected purposively. The data were collected through pre-tested schedule Form120 respondents selected randomly. The collected data were tabulated, analyzed and interpreted with the help of appropriate statistical tools. It was found that the majority of the famers adopted scientific recommendations like improved varieties, time of sowing, manual and chemical weed management while seed treatment and plant protection measures were not adopted by majority of the farmers due to lack of knowledge, high cost involved in purchasing agro-chemicals, use of sprayers in standing tall crop of for managing pod fly and food borers. Majority of farmers (58.33 %) were found having medium level of knowledge and attitude (55.84 %) towards Raised bed sowing of pigeonpea. Education and annual income had positive and significant correlation with their knowledge of improved technology of pigeonpea. Education had positive and significant association with their attitude towards raised bed sowing technique of pigeonpea.